DETERMINAN CAPITAL STRUCTURE SEKTOR INFRASTRUKTUR YANG TERDAFTAR DI BEI TAHUN 2017-2023 - MICHAEL BRYAN STEVEN; NILA PUSVIKASARI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study examines the factors influencing the capital structure of infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) during the period from 2017 to 2023. The analyzed factors include profitability, company size, asset structure, earnings volatility, and financial flexibility. This research is quantitative in nature and uses secondary data obtained from the companies' financial statements. The sample was determined using the purposive sampling method, and 119 data were obtained after conducting an outlier test. The data was then processed using descriptive statistical analysis, classical assumption tests, and hypothesis testing. Using panel data regression analysis, the results of the study indicate that profitability, asset structure, earnings volatility, and financial flexibility have a negative impact on capital structure. Meanwhile, company size shows a different result, positively influencing capital structure. The findings are expected to contribute to the development of knowledge regarding capital structure and its influencing factors. For company managers, the results can be used as a basis for capital structure decision-making. This study was conducted using only five independent variables, and it is recommended that future researchers expand the scope by adding other factors that may also affect capital structure. This study is just one among many on capital structure; the researcher recommends that readers delve deeper and explore more similar literature to broaden their understanding.